E-Sourcing platforms as reasonable marketing tools for suppliers - Martin Göbl; Thomas Greiter (Journal of Applied Leadership and Management, 2014)
Research questions: E-sourcing platforms offer purchasing organisations often easy access to a high number of relevant suppliers, their goods and services and the accord-ing prices. For the suppliers, e-sourcing platforms are a good and easy pos-sibility to present their products and services to the relevant buyers and to get in contact with potential customers. Subject of this research will be the question, whether e-sourcing platforms are also a reasonable marketing tool for suppliers in order to address the buyers with an assimilated market-ing mix.Methods: Guidelined expert interviews were chosen in order to ensure a comparabil-ity of the results without keeping the experts from contributing own ideas. Results: E-sourcing platforms are a proper way for suppliers to market their compa-nies and products in different ways. Thereby the preferred marketing measures differ according to criteria like the company size or the offered services or goods.
Keywords: 650